2016
DOI: 10.1039/c6dt03241a
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(0)-mediated C–O bond activation of ethers via an SN2 mechanism

Abstract: A computational study of the C(methyl)-O bond activation of fluorinated aryl methyl ethers by a platinum(0) complex Pt(PCyp) (Cyp = cyclopentyl) (N. A. Jasim, R. N. Perutz, B. Procacci and A. C. Whitwood, Chem. Commun., 2014, 50, 3914) demonstrates that the reaction proceeds via an S2 mechanism. Nucleophilic attack of Pt(0) generates an ion pair consisting of a T-shaped platinum cation with an agostic interaction with a cyclopentyl group and a fluoroaryloxy anion. This ion-pair is converted to a 4-coordinate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…The non-catalysed reaction of 1 with 2a was presumed to occur by an SN2 mechanism in which 1 act as an aluminium-centered nucleophile. 31,32 DFT calculations using the M06L functional and a hybrid basis-set support the proposal that such a mechanism is feasible (Figure 3a). SN2 attack occurs via TS-1 with a DG ‡ = 34.1 kcal mol -1 .…”
Section: Resultssupporting
confidence: 65%
“…The non-catalysed reaction of 1 with 2a was presumed to occur by an SN2 mechanism in which 1 act as an aluminium-centered nucleophile. 31,32 DFT calculations using the M06L functional and a hybrid basis-set support the proposal that such a mechanism is feasible (Figure 3a). SN2 attack occurs via TS-1 with a DG ‡ = 34.1 kcal mol -1 .…”
Section: Resultssupporting
confidence: 65%
“…The above discussion regarding the concerted mechanism gave us the impression that alkyl electrophiles remain almost inert to an external electric field. However, our computations show that unlike in the case of aryl electrophiles, alkyl electrophiles can undergo a facile S N 2-type mechanism for activation of the CH 3 –X bond. , In the field-free case, an S N 2-type mechanism is not possible due to the special electronic structure of the catalyst that possesses a σ-hole at the metal center (Figure a). However, when the field is switched on, the σ-hole on the catalyst is filled (Figure b) and the metal center is now nucleophilic enough to attack the CH 3 –X bond from the backside, leading to an S N 2-type TS.…”
Section: Resultsmentioning
confidence: 77%
“…The next step of the reaction is the C–O bond formation from the Pd(II)-complex 6 . Previous experimental and computational studies have demonstrated a complexity of the C–O bond formation from the Pd(II), Pt(IV), and Pd(IV)-complexes 46 53 . In 2001, Goldberg and coworkers concluded that the C(sp 3 )–O bond formation from the Pt(IV)-complex, likely, involves the OR – dissociation and following nucleophilic addition 46 .…”
Section: Resultsmentioning
confidence: 99%